A prototype of aerial radiation monitoring system using an unmanned helicopter mounting a GAGG scintillator Compton camera. Issue 7 (2nd July 2016) - Jiang, Jianyong; Shimazoe, Kenji; Nakamura, Yasuaki; Takahashi, Hiroyuki; Shikaze, Yoshiaki; Nishizawa, Yukiyasu; Yoshida, Mami; Sanada, Yukihisa; Torii, Tatsuo; Yoshino, Masao; Ito, Shigeki; Endo, Takanori; et al.
Abstract : Due to the accident of Fukushima Daiichi Nuclear Power Plant, some areas were contaminated by released radioisotopes (mainly 1 3 7 Cs and 1 3 4 Cs). Effective decontamination is demanded to encourage evacuated people to return. This paper proposes a new survey system using an unmanned helicopter equipped with a Compton camera for localizing radionuclides. As a prototype, 32 Ce:Gd3 (Al, Ga)5 O1 2 (GAGG) crystals were coupled to 16 silicon photomultipliers and 16 avalanched photodiodes as the scatterer and absorber, respectively. A new Dynamic Time-over-Threshold (dToT) method was applied to convert CR-RC shaping signals to digital signals for multi-channel spectra and coincidence acquisition. The system was designed to work in two modes: one is Compton-camera mode (CCM) which obtains the radiation distribution maps through Compton imaging using hovering flights, while the other one is Gamma-camera mode (GCM) which maps the radiation distribution via measured coincidence events using programmed flights. For point source in CCM, an intrinsic efficiency of 1.68% with a combined standard uncertainty of 0.04% and an angular resolution of about 14° (FWHM, full width at half maximum) was achieved. In GCM, a spatial resolution of about 11 cm (FWHM) was obtained when detecting area is 11.2 cm away from the detector, while it was about 28 cm (FWHM) in single detector mode (SDM). Promising results were obtained in field in Fukushima.